2022
DOI: 10.12765/cpos-2022-01
|View full text |Cite
|
Sign up to set email alerts
|

Internal Migration, Living Close to Family, and Individual Labour Market Outcomes in Spain

Abstract: Migration is often viewed as a way to enhance occupational careers. However, particularly in Mediterranean countries, labour market outcomes may also depend on local family resources. We investigate how men’s and women’s labour market outcomes differ between (1) those who migrated and those who did not; and (2) those who live close to family and those who live farther away. Our main contributions are the investigation of the association between migration and labour market outcomes in a different context than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…We see no reason to think that these individuals attached less importance to family and friends than professionals. Instead, we speculate that there may have been more respondents among the professionals (whose jobs are more likely to require migration; e.g., see Mulder et al, 2022 ) who have experienced living at a distance from their family and friends before. Furthermore, while we had expected to observe that people who had a university degree would be less likely to mention financial limitations than people who did not, we found no evidence for such an association.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…We see no reason to think that these individuals attached less importance to family and friends than professionals. Instead, we speculate that there may have been more respondents among the professionals (whose jobs are more likely to require migration; e.g., see Mulder et al, 2022 ) who have experienced living at a distance from their family and friends before. Furthermore, while we had expected to observe that people who had a university degree would be less likely to mention financial limitations than people who did not, we found no evidence for such an association.…”
Section: Resultsmentioning
confidence: 95%
“…We observed that many of the self-reported constraints to migration involved sources of non-transferable capital (i.e., local ties) that have previously been shown to act as constraints to migration (David et al, 2010 ; Michaelides, 2011 ; Mulder & Malmberg, 2014 ; Palomares-Linares, 2018 ; Thomassen, 2021 ) and financial constraints (Landale & Guest, 1985 ; Sjaastad, 1962 ). Some examples are ‘family care obligations’, ‘a fear of change’, ‘the work location’, or feeling ‘happy here’; obstacles such as age or health; and financial limitations such as ‘income’.…”
Section: Appendix 1: Operationalisation Of Self-reported Constraints ...mentioning
confidence: 82%
See 2 more Smart Citations
“…Among couples near retirement, consumer amenities become more important (Chen/Rosenthal 2008). Migrating towards family can also be benefi cial from an economic perspective as proximity to family members may protect people -women in particular -from precarious labour market positions (Mulder et al 2022) and increase their labour force attachment (Compton/Pollak 2014).…”
Section: Internal Migration and Educationmentioning
confidence: 99%